Pathways to a Successful Accountable Care Organization - Gross, Peter A., 1938- (Book collections on Project MUSE., 2020)
"Accountable Care Organizations arose from a provision in the Affordable Care Act. ACOs offer health care systems a chance to be rewarded financially for their performance, if they can meet quality benchmarks for patient health. Editor Peter Gross is the chairman of a successful ACO, and this collection explains how to institute such an organization and potential pitfalls one may encounter along the way. This book is aimed at hospital system administrators who are interested in making their own organization an ACO"--Provided by publisher.